Pengaruh Beban Kerja, Motivasi Kerja dan Kompetensi Terhadap Kepuasan Kerja Karyawan PT. Air Minum Giri Menang - Bagus Hari Sandika; Syaiful Amri; Faizatul Fajariah (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This study aims to determine the effect of Workload, Motivation and Competence on Job Satisfaction employees of PT. Air Minum Giri Menang (Perseroda) Mataram. The results of this study obtained that workload (X1) has a t test value where t count is smaller than t table, namely -0.353 <2.026 with a significant 0.726 > 0.05. Motivation (X2) has a significant effect on job satisfaction, this is evidenced by the results of the t test where t count is greater than t table, namely 4.024 > 2.026 with a significance of 0.000 <0.05. And competence (X3) has no significant effect on job satisfaction with a t count value that is smaller than t table of 0.742 <2.026 with a significant value of 0.463 > 0.05. While the simultaneous results of workload, motivation, and competence have a significant effect on job satisfaction. This is evidenced by the results of the simultaneous test (f) where the calculated f value is greater than the f table value, namely 9.481 > 2.859 with a significant value of 0.000 <0.05. The results of this study also show that the independent variables (workload, motivation and competence) are able to explain the dependent variable (job satisfaction) of 38.9% while the remaining 61.1% job satisfaction is influenced by other variables outside.